ANALISIS PENGARUH LINGKUNGAN KERJA DAN FASILITAS KERJA TERHADAP KINERJA KARYAWAN PT.TELKOM CABANG MERAUKE - Maria Kaok (EKONOMI & SOSIAL, 2019)
The purpose of this study was to analyze the influence of the work environment and work facilities on the performance of the employees of PT. Telkom (Engineering Section) Merauke Branch. With data analysis techniques using multiple linear regression analysis and t-test results of 3.567 for X1 variables (work environment) and X2 variables (work facilities) 2.16 and f-test 12.724. The conclusion of this research is that by paying attention to the work environment and adding work facilities it will have a good impact on employee performance.